Intercultural approach and reading comprehension in secondary education students, Simón Bolívar School – Mache - 2020 (SCIÉNDO INGENIUM, 2022)
The present research “Intercultural approach and reading comprehension in Secondary Education students, Simón Bolívar School, Mache 2020” is a study carried out to implement a programme based on the intercultural approach aiming to improve reading comprehension in English of third grade students from "Simón Bolívar” high school, Mache, 2020. The quasi-experimental design was applied, in which it was considered a "Pre-Test" and "Post-Test" with two intact groups. The sample in which this research was conducted was 53 students of third and fourth secondary students, in Mache District, Otuzco Province. A test consisting of 20 items designed to measure reading comprehension, which has three dimensions, was applied. The dimensions are literal, inferential and critical respectively, considering 10 for literal, 7 for inferential and 3 for critical.  It was concluded that the programme based on the Intercultural Approach significantly improves reading comprehension in English of the experimental group from Simón Bolívar School- Mache 2020.
Keywords: intercultural approach; reading comprehension; programme